The influence of Academic Sports Associations on the development of a sports career - Łosień, Tomasz; Mędrak, Anna; Plaskacz, Paweł; Bajerska, Izabela; Reut, Magdalena; Dragon, Emilia; Polko, Martyna; Cebula, Aleksandra (Journal of Education, Health and Sport, 2017)
Introduction: Young people who continue their education at universities do not have to give up their physical activity. The existence of Academic Sports Unions allows you to continue and develop your sporting career. A significant number of students regularly participating in AZS classes have a chance to develop their sporting career. The possibility of obtaining a sports scholarship is an additional motivation for students to pursue their own scientific and sporting goals. Sport through the process of self-improvement introduces a specific discipline to everyday life, teaches regularity, diligence and good organization of time.The aim of the study: 1) Did you start your education at a university by limiting or giving up sports?, 2) Do universities and AZS help develop a sports career? 3) Did the students of AZS influence the development of their sports career? Material and methods: 204 students participated in the study, an original questionnaire consisting of 26 questions was used. The questions concerned, among others: forms of physical activity and training experience, the impact of undertaking education at a university on the development of a sports career. Results and conclusions: Over 80% of respondents did not give up their sport before starting their studies. Over 50% of respondents believe that AZS and universities support the development of young athletes, giving the opportunity to get better and better results.